Toronto Clinical Neuropathy Score is valid for a wide spectrum of polyneuropathies. (26th December 2017) - Abraham, A.; Barnett, C.; Katzberg, H. D.; Lovblom, L. E.; Perkins, B. A.; Bril, V.
Abstract : Background and purpose: The Toronto Clinical Neuropathy Score (TCNS) is a valid and reliable scale for the diagnosis and staging of diabetic sensorimotor polyneuropathy. In this study, we aimed to explore the performance of the TCNS in non‐diabetic polyneuropathies. Methods: We performed a prospective study from November 2016 to May 2017 of patients with non‐diabetic polyneuropathy. Patients had clinical, electrophysiological and functional assessments of their polyneuropathy, and the findings were correlated with the TCNS. Results: The TCNS correlated with all clinical, electrophysiological and disability measures of polyneuropathy, mostly at a moderate level (e.g. r = −0.58 for sural nerve action potential amplitude). Higher TCNS severity grades were associated with worse polyneuropathy on all measures in the lower limbs, and with worse electrophysiological parameters and vibration perception thresholds in the upper limbs. The scale also showed excellent reliability and accuracy (kappa, 0.92–0.93 for inter‐ and intra‐observer reliability; area under the receiver operating characteristics curve, 0.93). Conclusion: The TCNS is a valid and reliable scale for a wide spectrum of polyneuropathies, and might be useful in clinical practise and research for the diagnosis and staging of polyneuropathy.